Jabatan Fungsional Penerjemah: Jembatan Indonesia ke Dunia Internasional - Abdini, Chairil (Jurnal Penerjemahan, 2014)
In today's domestic and international coniexts, the Ministry of State Secretariat fully realizes the importance and strategic position of translators/ interpreters and deems it necessary for the urgent appointment of highly qualified government translators/interpreters in all government agencies at the central and regional levels. To that end, this article discusses the efforts of the Ministry of State Secretariat to address this issue through the establishment of the Functional Positionof Translators. Furthermore, this article also discusses the various steps that have been taken by the Ministry of State Secretariat in its capacity as the Fostering Institution of the Functional Position of Translators.